Analyzing elements of text coherence in Khāvarān Nāma based on Halliday and Hassan's theory - Rowshan Rahmani; Shahrbanoo Haghshenas (مطالعات زبانی و بلاغی)
All texts are made up of single words, words and sentences that are put together for a specific purpose to convey a specific meaning or concept. A text is a longer unit than a sentence and becomes a discourse when it is coherent. In coherence theory, text analysis is at the core of all readings. In fact, the author reflects his real and meta-real world with the help of language and maintaining the relationship between the elements that make up the text, adding to the semantic depth, effectiveness and allure of the text as well as its appeal to the audience. The present study analyzed the elements of the text coherence in Ibn Hussām Khosfi's Khāvarān Nāma, using Halliday and Hassan’s text coherence theory (1976 AD), in the two categories of "grammatical and lexical". One finding of this research is that lexical and semantic elements, especially the element of repetition, are the first and foremost factor of coherence and cohesion of the text. Considering that the Khāvarān Nāma is an epic-narrative text from the omniscient point of view, the text has a central axis and the reference of pronouns in the sentences, as another important factor in text coherence, is both limited and specific. What creates this unity and coherence is the poet’s profound thought, which flows in the longitudinal axis of the poems.